2010
DOI: 10.1248/cpb.58.1306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Antioxidant Activities, and DNA-Binding Studies of (<i>E</i>)-<i>N</i>&prime;-[1-(Pyridin-2-yl)ethylidene]isonicotinohydrazide and Its Pr(III) and Nd(III) Complexes

Abstract: It is well-known that Schiff bases play important role in bioinorganic chemistry and their metal complexes have been studied extensively for decades. These interesting ligand systems contain different donor sites in heterocyclic rings, e.g., NNO or NNS, which give rise to the architectural beauty of these coordination complexes.1) Among the ligand systems, hydrazide and hydrazone occupy important places because transition metal complexes of these ligands have been developed due to their chelating capability, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The vibrations ν(N-H) disappeared in the spectra of the four complexes, indicating that the ligand was deprotonated. The novel bands near 560 cm -1 for the complexes were assigned to ν(M-O), and the weaker peaks near 470 cm -1 were assigned to ν(M-N), respectively (23,24), consistent with the results of X-ray diffraction analysis.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The vibrations ν(N-H) disappeared in the spectra of the four complexes, indicating that the ligand was deprotonated. The novel bands near 560 cm -1 for the complexes were assigned to ν(M-O), and the weaker peaks near 470 cm -1 were assigned to ν(M-N), respectively (23,24), consistent with the results of X-ray diffraction analysis.…”
Section: Resultssupporting
confidence: 83%
“…It has been reported that arylhydrazone and its metal complexes exhibit markedly effective antitumor activities, possibly due to their NO bidentate systems (24). In vitro cytotoxicity assays were carried out in the human A549 (human lung cancer), BGC823 (human gastric cancer) and Eca109 (human esophageal cancer) solid tumor cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand penh was synthesized according to the literature method while nicotinoyl hydrazide instead of isonicotinoyl hydrazide [19] . Yield, 93.1%.…”
Section: Preparation Of the Ligandmentioning
confidence: 99%
“…The ligand HL was prepared as described previously (20). In brief, HL was obtained by condensation of 2-acetylpyridine (0.1 mmol) and isonicotinohydrazone (0.1 mmol) in ethanol solution with the addition of 0.1 ml concentrated acetic acid.…”
Section: Materials and Measurementsmentioning
confidence: 99%